Mobility Comparisons: Theoretical Definitions and People’s Perceptions - Michele Bernasconi; Giulio Cinquanta; Valentino Dardanoni; Vincenzo Prete (Games, 2025)
Comparing mobility is an important but controversial issue. In this paper, we argue that in a specific and relevant case, there exists a univocal and non-controversial definition of greater (exchange) mobility that allows for unambiguous comparisons. We conducted a questionnaire experiment to investigate whether people’s perceptions of social mobility align with this definition, and we found that people’s choices are broadly in line with the theoretical predictions.